Exploring Key Themes in Halal Tourism Studies: A Systematic Literature Review Approach - Lestari, Puput; Hidayah, Risa Nur (IPB University, 2025)
Halal tourism has grown rapidly over the past two decades, becoming a strategic pillar of the global industry. The expansion of the Muslim travel market, reaching millions of international arrivals annually, underscores the growing need for destinations, products, and services consistent with Islamic values. Therefore, this study aims to identify major themes and gaps in the halal tourism literature through a Systematic Literature Review (SLR) based on PRISMA guidelines. Using the keyword “halal tourism” in the Scopus database (2014–2025), a total of 659 articles were initially retrieved, with 31 fulfilling the final inclusion criteria after screening for access, language, and relevance. The results showed that Indonesia dominates halal tourism literature (28 articles), with case studies and surveys being the most common methods. Thematically, studies cluster into nine categories, namely Muslim tourist behavior and loyalty, policy and governance, branding and promotion, religious moderation and local wisdom, destination strategies, halal food consumption, technology and digitalization, literacy and social capital, as well as certification. Previous studies have largely focused on tourist behavior, while implementation and certification remain underexplored. In general, halal tourism is a multidimensional field integrating culture, governance, branding, and technology beyond mere compliance with Islamic law. Future studies should focus on practical implementation, certification systems, and digital transformation. Strengthening these areas will enhance competitiveness, ensure inclusivity for Muslim travelers, and support the sustainability of halal tourism as a driver of equitable growth in the global landscape.